Development of a wind turbine with two multidirectional wind wheels - Issenov, Sultanbek; Antipov, Pyotr; Koshumbayev, Marat; Issabekov, Dauren (Eastern-European Journal of Enterprise Technologies, 2024)
The object of research is a wind generator with counter-rotating blades. A special feature of this design is the presence of two wind wheels that rotate in opposite directions. Wind wheels are on the same axis, between them there is a certain distance, which is determined based on research data. The problem of modern wind power is the low range of operating wind speeds, weak generation at low wind speeds. The upper speed limit is 25 m/s, exceeding which leads to breakdowns of various units of the wind station, especially this affects the integrity of the blades, rupture of the wind wheel, cracking of the metal parts of the bearings and their fasteners. The wind turbine presented in the article allows to achieve an increase in the generation of electric energy by 50–70 %. This is achieved by increasing the relative rotational speed of the rotor relative to the stator. Therefore, even at low speeds, the rotor speed relative to the stator increases, which leads to an increase in power generation. The design of the device includes: two wind wheels, one transmits its rotation to the stator, the second to the rotor axis, a metal base, a current collector mechanism. For conducting the research, an experimental model and a semi-industrial installation were used. Results studies have confirmed the theoretical increase in the generation of electrical energy by this design. The peculiarity of the obtained results is connected with the determination of the distance between two wind wheels, the optimal distance between them corresponds to the maximum energy generation. A distinctive feature of the results obtained can be considered an increase in the number of blades on the second wind wheel